Harvey Milk's (sexual and sacred) body. (24th July 2022) - Gilders, William K
Abstract : Harvey Milk has been constituted as a queer saint. This article, in the self-identifying voice of a gay man, explores the significance of Harvey Milk's queer cultural sanctity in relation to his sexual embodiment, emphasizing that 'Saint Harvey' was a leading figure in a movement of sexual liberation and was himself a strongly sexual being, facts sometimes downplayed in his representation as a sacred figure in contrast with his vitally sexual pre-assassination body. Examining the phenomenon of the 'canonization' of a sexually embodied gay Jewish agnostic, the article asks what happens when Milk's sacralization is explicitly tied to his sexuality, focusing on a central question: can a saint be a sexual being, not peripherally or incidentally, but centrally and essentially?